Financial Keynesianism and market instability - L. Randall Wray (Levy Economics Institute of Bard College, 2011)
In this paper I will follow Hyman Minsky in arguing that the postwar period has seen a slow transformation of the economy from a structure that could be characterized as robust to one that is fragile. While many economists and policymakers have argued that no one saw it coming, Minsky and his followers certainly did! While some of the details might have surprised Minsky, certainly the general contours of this crisis were foreseen by him a half century ago. I will focus on two main points: first, the past four decades have seen the return of finance capitalism and second, the collapse that began two years ago is a classic Fisher-Minsky debt deflation. The appropriate way to analyze this transformation and collapse is from the perspective of what Minsky called financial Keynesianism - a label he preferred over Post Keynesian because it emphasized the financial nature of the capitalist economy he analyzed.
Keywords: B22; B25; B26; B52; E02; E11; E12; E44; G01; G18; G20; G21; 330; Hyman Minsky; Fisher-Minsky debt deflation; Hilferding; finance capitalism; money manager capitalism; financial Keynesian